(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The striped owl (Asioclamator) is unique with its brownish white facial disc and they are found in the north eastern part of Nigeria. Little is known in the literature on the basic neuroanatomy of this species. This study focuses on the histology and glial expression of some brain regions of the striped owl. Five owls were obtained in the wild, and their brains were routinely prepared for Haematoxylin and Eosin, and Cresyl violet staining. Immunostaining was done with anti-Calbindin, anti MBP, anti-GFAP, and anti-Iba-1 antibodies; for the expression of cerebellar Purkinje cells and white matter, cerebral astrocytes and microglia cells respectively. These were qualitatively described. We found that the hippocampal formation of the striped owl, though unique, is very similar to what is seen in mammals. The cerebellar cortex is convoluted, has a single layer of Purkinje cells with profuse dendritic arborization, a distinct external granular cell layer, and a prominent stem of white matter were seen in this study. The astrocytic population in cerebral gray is similar, though lacking in many processes as is typical in protoplasmic astrocytes, while the microglia were not strongly stained. The few stained microglia cells did not, however, show any features of activation. The striped owl’s brain reveals some conserved aspects of cellular neuroanatomy in both the avian and mammals that are typical in these species. More work is however needed particularly in age related differences in these structures. This is perhaps the first report of Calbindin immunostaining in the brain of the striped owl.